ANALISIS PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Julianan Nasution; Riska Adwiyah Hasibuan; Kharisa Abdi; Fadlul Rohman (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The purpose of this study was to determine the analysis of the influence of the implementation of good corporate governance in the company. Corporate Governance is corporate governance that explains the relationship of the parties participating in the management and performance of the company. This article was compiled based on data and references obtained from scientific journals related to the discussion. This writing method is a literature study and the data that has been collected is arranged and sorted logically and systematically. The results obtained in this study are: 1) Managerial Ownership has a significant positive effect on firm value. 2) Institutional ownership has a positive and insignificant effect on firm value. 3) The Audit Committee has a positive and insignificant effect on firm value. 4) The proportion of independent commissioners has a significant positive effect on firm value. 5) External auditors have a positive and insignificant effect on firm value.